Supporting Six Aspects of Development of Children 3-6 Years Through Educational Educative Tools Smart Book - Anggraini, Retno; Suyadi, Suyadi (Indonesian Journal of Early Childhood Education Studies, 2019)
Educational play equipment (APE) is a tool that was made intentionally so that it can be used as a means or play tool, which contains several educational values, and can develop several aspects of child development in a single, multipurpose and safe tool for children. The purpose of this research is to apply and apply an APE named Smart Book, which can support six aspects of the development of children aged 3-6 years. The study was conducted in November and carried out at the Playgroup and Kindergarten Star Kids Yogyakarta. Smart book APE has been designed and in it there are several materials such as the introduction of colors, numbers, letters, professions, prayer times, sequence Sholat, ablution and so on. The focus of this research is to describe the facts of the use of APE smart books that can support six aspects of the development of children aged 3-6 years. The results obtained were based on observations of the implementation of the use of APE smart books in Palygroup and Kindergarten Star Kids Yogyakarta, that six aspects of child development can be developed through smart books, namely cognitive, fine motor, language, religious, and social emotional aspects. Keywords: APE, smart book, six aspects of development, children